The Effectiveness of an Electronic Training Program Using Collaborative Groups on Developing Teachers’ Teaching Competencies of Health and Physical Education at The Primary Level - Al-Quhaiz, Nasser Mohammed; Al-Jassas, Rashid Mohammed; Al-Fayez, Abdulaziz Abdullah (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the effectiveness of an electronic training program using collaborative groups in developing the teaching competencies of health and physical education teachers at the primary stage. The study population consisted of all health and physical education teachers at the primary stage in the Education Department in Al-Kharj Governorate, and their number was (87) teachers. The study sample was chosen randomly, and their number was (24) teachers. The study tool was (observation card) built by the researcher to determine the effectiveness of the training program for developing competencies (planning, implementation, evaluation). The results showed that there were statistically significant differences at the level ( ≤ 0.01) between the mean scores of the study sample in the pre and post measurements on the observation card in competencies (planning, implementation, evaluation) according to the electronic training program using collaborative groups. The differences were in favor of the telemetry with an effect size of (2.45) in planning competencies, (2.02) in implementation competencies, (2.11) in evaluation competencies; Which is a very large effect according to Cohen's criteria. The study recommended: making use of the e-training program using the method of collaborative groups in developing teaching competencies.
Keywords: Teaching Competencies; Program; Electronic Training; Cooperative Groups; Health and Physical Education Teachers